Efek Ekstrak Daun Alpukat (Persea americana Mill.) dalam Menurunkan Kadar Kolesterol Darah pada Mencit (Mus Musculus) - Mufida, Mufida; Rahman, Nurdin; Supriadi, Supriadi (Jurnal Akademika Kimia, 2018)
This study aimed to determine the effective concentration of avocado leaves extract in lowering cholesterol blood levels in mice (Mus musculus). The animals test were 15 male mice and were induced with propylthiouracil and high-fat dietary food. Mice were divided randomly into 5 groups with different treatments. Treatments I, II and III were given avocado leaves extracts each with a concentration of 10, 20, and 40%, respectively. Treatment IV was given simvastatin suspension as a positive control, and treatment V was given (Na-CMC) 1% as a negative control. Data were analyzed statistically with analysis of variance (ANOVA) test followed by Duncan test. The results showed that avocado leaves extract contained positively of alkaloids, flavonoids, saponins, tannins, and triterpenoid or steroids. Avocado leaves extract lowered cholesterol blood levels in mice with the most effective concentration was 10% (w/v).